Deciphering archeological contexts from the magnetic map: Determination of daub distribution and mass of Chalcolithic house remains. (October 2019) - Pickartz, Natalie; Hofmann, Robert; Dreibrodt, Stefan; Rassmann, Knut; Shatilo, Liudmyla; Ohlrau, René; Wilken, Dennis; Rabbel, Wolfgang
The unique size and development of prehistoric megasites of the north Pontic Cucuteni-Tripolye Chalcolithic groups (4100–3600 BCE) challenge modern archeology and paleoecology. The extremely large number of houses (approximately 3000, mostly burned) necessitates the development of multidisciplinary technologies to gain a holistic understanding of such sites. In this contribution, we introduce a novel geophysical methodology and a detailed analysis of magnetic data – including evolved modeling techniques – to provide critical information about the setup of findings, enabling a thorough understanding of the settlement dynamics, apart from invasive excavation techniques. The case study is based on data from magnetic field maps and distribution maps of the daub and pottery find categories. This information is used to infer magnetic models for each find category to numerically calculate their magnetic fields for comparison with the archeological data. The comparison quantifies the sensitivity of the magnetic measurements with respect to the distribution of the different find categories. Next, via inversion computation, the characteristic depth functions of soil magnetization are used to generate maps of magnetization from the measured magnetic field maps. To validate the inverted soil magnetization maps, the magnetic excavation models are used, providing an interpretational frame for the application to magnetic anomalies outside excavated areas. This joint magnetic and archeological methodology allows estimating the find density and testing hypotheses about the burning processes of the houses. In this paper, we show internal patterns of burned houses, comparable to archeological house models, and their calculated masses as examples of the methodology. An application of the new approach to complete megasites has the potential to enable a better understanding of the settlement structure and its evolution, improve the quality of population estimations, and thus calculate the human impact on the forest steppe environment and address questions of resilience and carrying capacity.